A 1H NMR based study of hemolymph metabonomics in different resistant silkworms, Bombyx mori (Lepidotera), after BmNPV inoculation. (August 2019) - Wang, Xue-yang; Shao, Zuo-min; Zhang, Ying-jian; Vu, Thi Thuy; Wu, Yang-chun; Xu, Jia-ping; Deng, Ming-jie
Graphical abstract: Highlights: The persistent upregulation of trehalose plays a vital role in response to BmNPV infection. A regular upregulation of TCA cycle related metabolites in resistant strains is involved in defense against BmNPV infection. Significant variations in Branched-chain amino acid (BCAA) indicates it's roles in BmNPV infection. Abstract: Bombyx mori nucleopolyhedrovirus (BmNPV) is a primary silkworm pathogen, and the molecular mechanism of silkworm defense to BmNPV infection is still unclear. Herein, comparative metabolomics was adopted to analyze the variations in the hemolymph metabolites of different resistant silkworm strains following BmNPV inoculation using a 1 H NMR method. Trehalose, as an instant source of energy, plays a crucial role in the response to pathogen infections in insects. The level of trehalose was persistently upregulated in the hemolymph of the resistant silkworm strain YeA following infection with BmNPV, compared to that of the susceptible strain YeB, indicating that trehalose metabolism plays a vital role in the response to BmNPV infection. The significant upregulation of TCA cycle relevant metabolites, including malate, fumarate, citrate, succinate, and α-ketoglutarate, was identified at 0 h, 12 h, 48 h, and 96 h post-infection in YeA hemolymph, whereas a significant upregulation in YeB hemolymph was only detected at an early stage of infection (0 h–24 h). The expression level of selected key metabolic enzymes, determined using RT-qPCR, validated the differences in trehalose and TCA cycle relevant metabolite levels. The variations in branched-chain amino acid (BCAA) pathway relevant metabolites in resistant silkworm strains following BmNPV infection showed a regular undulation at different times after infection. A significant accumulation of phenylalanine and tyrosine was observed in YeA following BmNPV infection compared to YeB. The glycolysis and gluconeogenesis pathways showed a relatively low activity in YeA following BmNPV infection. Moreover, the levels of other metabolites related to fat metabolism, transamination, energy metabolism, and glycometabolism, such as glycine, threonine, glutamine, and glutamate, were unstable in the two silkworm strains following BmNPV infection. Thus, our study provides an overview of the metabolic response of the silkworm in response to BmNPV infection, which lays the foundation for clarifying the mechanism of silkworm resistance to BmNPV infection.